Learning about Internal Capital Markets from Corporate Spin‐offs - Gertner, Robert; Powers, Eric; Scharfstein, David (Journal of Finance, 2002)
We examine the investment behavior of firms before and after being spun off from their parent companies. Their investment after the spin‐off is significantly more sensitive to measures of investment opportunities (e.g., industry Tobin's Q or industry investment) than it is before the spin‐off. Spin‐offs tend to cut investment in low Q industries and increase investment in high Q industries. These changes are observed primarily in spin‐offs of firms in industries unrelated to the parents' industries and in spin‐offs where the stock market reacts favorably to the spin‐off announcement. Our findings suggest that spin‐offs may improve the allocation of capital.